The study of watermelon rind (Citrullus lanatus) and pinenapple fruit (Ananas comosus L.) proportion with caragenan addition on fruit leather physicochemical characteristics - Devi Dwi Siskawardani Rias Anggun Kartika, Warkoyo Khusnul Khotimah (Food Technology and Halal Science Journal, 2019)
presentage of pectin is about 21.03% which suitable for food production such as fruit leather. Fruit leather is one of the snack food products from fruit pulp (puree) were dried in an oven or a dehydrator. Shortage of watermelon rind fruit leather is to produce flavor and color that is less interesting and has a less flexible texture. Therefore, in making fruit leather from watermelon rind is added substitution materials and stabilizers such as pineapple and carrageenan. This study aimed to determine the effect of the proportion of watermelon rind with pineapple and the addition of carrageenan concentration on the physicochemical and sensory characteristics of fruit leather. The study was conducted using a randomized complete block design (RCBD) factorial. The first factor with three levels, namely the proportion of watermelon rind and pineapple (90%:10%, 80%:20%, and 70%:30%). The second factor was carrageenan concentration (0,2%, 0,4%, and 0,6%). Treatment of the proportion of watermelon rind and pineapple had significant effect on water content, ash, vitamin C, hardness, sugar, lightness (L), yellowish (b+). Treatment of carrageenan concentration has significant effect on water content, ash, vitamin C, lightness (L). Fruit leather of watermelon rind that has best physicochemical characteristics was A1K1 treatment is the proportion of albedo rind and pineapple (90%: 10%) and carrageenan concentration 0.2%. organoleptic taste 3.10, aroma 2.70, color 3.00, and favor 3.03.